The bonding modes and optical characteristics of annealed silicon oxide thin films prepared by plasma enhanced CVD - Tan, K.H.; Muhamad, MR. (Malaysian Journal of Science, 2017)
Silicon oxide (SiO , 0 < x < 2) thin films have been prepared by the plasma enhanced CVD of gaseous silane and nitrous oxide (flow rate ratio 2/1) onto quartz and silicon wafer substrates at 2500C. The samples were then annealed in ambient oxygen at 100 to 6000C at intervals of 100 degrees. The Si-O-Si bending and stretching, Si-H stretching and Si-OH stretching modes were identified from the infrared spectra. The annealing process resulted in an excess of tetrahedral Si04 units and the generation of dangling bonds.